Global PBL: Cross-cultural educational project for engineering students - Navas, Helena V.G. (2020)
Project-Based Learning (PBL) has been the active learning methodology used in a Cross-Cultural Engineering Project (CEP) that it is an educational project between Shibaura Institute of Technology (SIT) from Japan, NOVA School of Science and Technology (FCT NOVA), Universidade NOVA de Lisboa from Portugal and King Mongkut's University of Technology, Thonburi (KMUTT) from Thailand. This partnership occurred since July 2017, so three successful editions were achieved. The editions last nine days and were held in mid-July. The venue of the event was the Caparica Campus of the NOVA School of Science and Technology (FCT NOVA). The hard core of course participants are students from SIT (Japan), KMUTT (Thailand) and FCT NOVA (Portugal). Students from the Chulalongkorn University (Chula. Univ.) and Chiang Mai University (CMU) from Thailand and from University of Navarra of Spain had also participated in some editions of the event. More than 100 students, 20 teaching assistants and 10 teachers were involved on this global PBL on the three editions. The students were organized in interdisciplinary and international four or five teams of different graduate and undergraduate years, of different universities. Each team had to work in a contemporary problem related with Ecology, Energy, Eco-tourism, Community development among others. This paper presents the results of such experience, pointing out the benefits for the students and for the teachers. A discussion about the competencies acquired by the students is presented. Some challenges are also addressed.